The Relationship Between Long-Term Type 2 Diabetes Mellitus (T2DM) and Uric Acid Levels in DM Patients at Klinik Iman - Fatimah Zahra; Des Suryani (JURNAL IMPLEMENTA HUSADA, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease associated with purine metabolism disorders that may lead to increased uric acid levels. The duration of the disease, along with blood sugar control and cholesterol levels, can worsen metabolic control and increase the risk of hyperuricemia. This study aimed to determine the relationship between the duration of T2DM and uric acid levels, as well as the influence of blood sugar and cholesterol levels on uric acid levels in T2DM patients. This study was conducted at Klinik Iman from September to October 2025. Data were collected from 32 respondents, including duration of T2DM, uric acid, blood sugar, and cholesterol levels. Data analysis was performed using the Kruskal-Wallis and Chi-Square tests according to data distribution. The results showed a significant relationship between the duration of T2DM and uric acid levels (p 0,05). This relationship was also associated with blood sugar levels (p 0,05). A significant relationship was found between the duration of T2DM and cholesterol levels (p 0,05), as well as between cholesterol and uric acid levels (p 0,05). Therefore, controlling blood sugar and cholesterol levels is important to prevent hyperuricemia in T2DM patients.